Training on Journal Management and Index of Social Sciences and Public Administration Journals for Lecturers - Nahruddin, Zulfan (Journal of Universal Community Empowerment Provision, 2023)
This study aims to investigate the effectiveness of training programs designed for lecturers involved in managing social sciences and public administration journals. It focuses on understanding the components of these training programs, evaluating their impact on journal management skills, and exploring case studies and best practices to provide a comprehensive overview of successful journal management strategies. Comprehensive training programs significantly enhance the journal management skills of lecturers. Key components of effective training include editorial process management, ethical standards enforcement, understanding and leveraging journal metrics, technical and administrative proficiency, and marketing and outreach strategies. Trained journal managers demonstrate improved efficiency in handling submissions, conducting peer reviews, and maintaining high ethical standards. The implementation of best practices, such as rigorous peer review processes and effective marketing strategies, leads to increased journal visibility, higher citation rates, and enhanced overall impact.